Health Education with Media Leaflet Against Women's Knowledge of Cervical Cancer Screening: Pendidikan Kesehatan dengan Media Leaflet Terhadap Pengetahuan Wanita tentang Skrining Kanker Serviks - Sumiaty, Sumiaty; Hasnawati, Hasnawati (Poltekkes Kemenkes Palu, 2022)
Background: Cervical cancer is the second-leading cancer of death in women in Indonesia. The prevalence of cancer in Central Sulawesi Province increased from 0.9% to 2.3%. The low number of early detection examinations of cervical cancer in Central Sulawesi Province aged 30-50 years is only 8.06%. Objective: to determine the effect of health education using leaflet media on the knowledge of women of childbearing age about cervical cancer screening. Methods: Quasy experimental with one group pre-posttest design without control. The sample number of 32 women of childbearing age with purposive sampling techniques. The data is analyzed with univariate tests and bivariate tests. Bivariate test analysis using Paired t-test Results: The average knowledge value before being given health education is 59.06 and after obtaining health education is 86.16. Average increase in knowledge of 27.10 with a Pvalue value of 0.000. Conclusion: There is an effect of health education with leaflet media on women's knowledge about cervical cancer screening. It is expected that health workers will regularly provide health education.